Efeitos do uso de probióticos na microbiota intestinal, estado clínico-nutricional e imunológico de pacientes gastrectomizados por câncer gástrico: um ensaio clínico randomizado – PRONIC-G - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
Introduction: Gastric cancer (GC) is the fifth most common neoplasm in the world, with more than 1 million new cases per year. The most accepted etiology is based on the influence of tissue mutation promoted by a bacterium from the gastric commensal microbiota called H. pylori. The gold standard treatment for gastric cancer is surgery to remove all or part of the stomach. Surgery has great power to modify the human microbiota, whose changes are still poorly understood in Amazonas. Several factors can also contribute to changes in the intestinal microbiota in patients with gastric cancer, which can culminate in both the worsening of clinical outcomes and the modification of the intestinal microbiota profile, combined with the impairment of the immunological response pattern, however data corroborating This statement is scarce, which motivated the study of the intestinal microbiota in the Amazonian population. Objectives: To evaluate the intestinal microbiota profile, nutritional, immunological status and inflammatory profile, before and after surgery to remove total or partial stomach (gastrectomy) for gastric cancer in patients who used probiotic supplements. Materials and methods: This is a randomized controlled, prospective clinical study, composed of five groups – G1, G2, G3, G4 and G5, where we evaluated the use of probiotics, both in modulating the immune response and in the intestinal microbiota profile and reducing surgical complications. Results: In the first period of the study, from December 2020 to May 2022, 24 patients were evaluated, with a mean age of 58.8±14.4 years (range 24 to 81 years), the majority of whom were male (70.8%) and with adenocarcinoma (83.3%). Regarding clinical variables, such as arm muscle circumference (P=0.006), phase angle (P= <0.001), adductor pollicis muscle thickness (P=0.005) and especially fecal calprotectin (P=<0.001). Regarding inflammatory cytokines, it was demonstrated that there were no statistically significant differences when comparing the probiotic and non-probiotic groups, however the group using probiotics seems to have responded well to some cytokines (CXCL-8, TNF-α, IL-17a, IL-4) (p-value >0.05), of which IL-17a was the cytokine that was most statistically significant (p-value <0.001). Data from the intestinal microbiota demonstrated that one phylum was noteworthy, Proteobacteria, with 10.4%, which demonstrates a pattern of dysbiosis in the cancer group. Regarding the genera, the one with the greatest abundance was Streptococcus (p-value 0.019); when comparing comparisons between microbiota and cytokines, Alloprevotella (p-value 0.004) and Christensenellaceae_R-7_group (p-value 0.01) were differentially abundant, but reduced in the context of many complications, with Alloprevotella being a biomarker for gastric cancer. In the second phase of the study, a total of 52 patients were evaluated, whose most common complication was nausea and vomiting (N=39, 75%). There was a higher percentage of those classified as having many complications (60%) in the probiotic (+) group, which therefore shows that there was no positive interference in reducing complications when using seven days of probiotics according to the protocol of this study. Conclusion: It is possible to infer that cancer plays an important role in maintaining intestinal dysbiosis and that a longer period of probiotic use should be considered so that there is intestinal modulation of the microbiota and the inflammatory profile in patients with gastric cancer.
Keywords: .; .; .; CIENCIAS BIOLOGICAS; Neoplasias gástricas; Câncer; Microbioma gastrointestinal; Estado nutricional; Fatores imunológicos